Skip to main content

A new reverse Hardy–Hilbert inequality with the power function as intermediate variables

Abstract

In this paper, by virtue of the symmetry principle, applying the techniques of real analysis and Euler–Maclaurin summation formula, we construct proper weight coefficients and use them to establish a reverse Hardy–Hilbert inequality with the power function as intermediate variables. Then, we obtain the equivalent forms and some equivalent statements of the best possible constant factor related to several parameters. Finally, we illustrate how the obtained results can generate some particular reverse Hardy–Hilbert inequalities.

Introduction

Suppose that \(p > 1\), \(\frac{1}{p} + \frac{1}{q} = 1\), \(a_{m},b_{n} \ge 0\), \(0 < \sum_{m = 1}^{\infty } a_{m}^{p} < \infty \), and \(0 < \sum_{n = 1}^{\infty } b_{n}^{q} < \infty \). We have the following well-known Hardy–Hilbert inequality with the best possible constant factor \(\frac{\pi }{\sin (\pi /p)}\) (cf. [1], Theorem 315):

$$ \sum_{m = 1}^{\infty } \sum _{n = 1}^{\infty } \frac{a_{m}b_{n}}{m + n} < \frac{\pi }{\sin (\pi /p)} \Biggl(\sum_{m = 1}^{\infty } a_{m}^{p} \Biggr)^{\frac{1}{p}}\Biggl(\sum_{n = 1}^{\infty } b_{n}^{q} \Biggr)^{\frac{1}{q}}. $$
(1)

In 2006, by introducing multi parameters \(\lambda _{i} \in (0,2]\) (\(i = 1,2\)), \(\lambda _{1} + \lambda _{2} = \lambda \in (0,4]\),an extension of (1) was provided by Krnić et al. [2] as follows:

$$ \sum_{m = 1}^{\infty } \sum _{n = 1}^{\infty } \frac{a_{m}b_{n}}{(m + n)^{\lambda }} < B(\lambda _{1},\lambda _{2})\Biggl[\sum_{m = 1}^{\infty } m^{p(1 - \lambda _{1}) - 1}a_{m}^{p} \Biggr]^{\frac{1}{p}}\Biggl[\sum _{n = 1}^{\infty } n^{q(1 - \lambda _{2}) - 1}b_{n}^{q} \Biggr]^{\frac{1}{q}}, $$
(2)

where the constant factor \(B(\lambda _{1},\lambda _{2})\) is the best possible and

$$ B(u,v) = \int _{0}^{\infty } \frac{t^{u - 1}}{(1 + t)^{u + v}}\,dt\quad (u,v > 0) $$
(3)

is the beta function. For \(p = q = 2\), \(\lambda _{1} = \lambda _{2} = \frac{\lambda }{2}\), inequality (2) reduces to Yang’s inequality in [3] as follows:

$$ \sum_{m = 1}^{\infty } \sum _{n = 1}^{\infty } \frac{a_{m}b_{n}}{(m + n)^{\lambda }} < B\biggl( \frac{\lambda }{2},\frac{\lambda }{2}\biggr) \Biggl(\sum _{m = 1}^{\infty } m^{1 - \lambda } a_{m}^{2} \sum_{n = 1}^{\infty } n^{1 - \lambda } b_{n}^{2} \Biggr)^{\frac{1}{2}}. $$
(4)

Recently, by using inequality (2), Adiyasuren et al. [4] gave a new Hardy–Hilbert inequality with the best possible constant factor \(\lambda _{1}\lambda _{2}B(\lambda _{1},\lambda _{2})\) involving two partial sums as follows: For \(\lambda _{i} \in (0,1] \cap (0,\lambda )\) (\(i = 1,2\)), \(\lambda _{1} + \lambda _{2} = \lambda \in (0,2]\), we have

$$ \sum_{m = 1}^{\infty } \sum _{n = 1}^{\infty } \frac{a_{m}b_{n}}{(m + n)^{\lambda }} < \lambda _{1} \lambda _{2}B(\lambda _{1},\lambda _{2}) \Biggl( \sum_{m = 1}^{\infty } m^{ - p\lambda _{1} - 1} A_{m}^{p}\Biggr)^{\frac{1}{p}}\Biggl(\sum _{n = 1}^{\infty } n^{ - q\lambda _{2} - 1} B_{n}^{q} \Biggr)^{\frac{1}{q}}, $$
(5)

where, for \(a_{m},b_{n} \ge 0\), two partial sums \(A_{m} = \sum_{i = 1}^{m} a_{i}\) \(B_{n} = \sum_{k = 1}^{n} b_{k}\) are indicated, satisfying

$$ 0 < \sum_{m = 1}^{\infty } m^{ - p\lambda _{1} - 1} A_{m}^{p} < \infty \quad \text{and}\quad 0 < \sum _{n = 1}^{\infty } n^{ - q\lambda _{2} - 1} B_{n}^{q} < \infty . $$

Inequalities (1) and (2) with their integral analogues and the reverses play an important role in the analysis and its applications (cf. [516]).

In 1934, a half-discrete Hilbert-type inequality was given as follows (cf. [1], Theorem 351): If \(K(t)\) (\(t > 0\)) is a decreasing function, \(p > 1\), \(\frac{1}{p} + \frac{1}{q} = 1\), \(0 < \phi (s) = \int _{0}^{\infty } K(t)t^{s - 1}\,dt < \infty \), \(a_{n} \ge 0\), \(0 < \sum_{n = 1}^{\infty } a_{n}^{p} < \infty \), then we have

$$ \int _{0}^{\infty } x^{p - 2}\Biggl(\sum _{n = 1}^{\infty } K(nx)a_{n} \Biggr)^{p}\,dx < \phi ^{p}\biggl(\frac{1}{q}\biggr)\sum _{n = 1}^{\infty } a_{n}^{p}. $$
(6)

Some new extensions of (6) with their reverses were provided by [1722].

In 2016, Hong et al. [23] obtained some equivalent statements of the extensions of (1) with the best possible constant factor related to several parameters. The other similar works were given by [2431]. In 2019–2020, Luo et al. [32] considered a new inequality of the extension of (2) with the general decreasing kernel as \(k_{\lambda } (m^{\alpha },n^{\beta } )\) (\(\lambda ,\alpha ,\beta > 0\)); Huang et al. [33] also gave a reverse of (2) by using the Euler–Maclaurin summation formula.

In this paper, following the way of [2, 23], by virtue of the symmetry principle, by means of the weight coefficients, the idea of introduced parameters, and the techniques of real analysis, we apply the Euler–Maclaurin summation formula to provide a reverse Hardy–Hilbert inequality with the kernel as follows:

$$ \frac{1}{(m^{\alpha } + n^{\beta } ){}^{\lambda }}\quad (\lambda \in (0,6],\alpha ,\beta \in (0,1]), $$

which is an extension of [33]’s work. The equivalent forms, some equivalent statements of the best possible constant factor related to several parameters, and some particular inequalities are also obtained.

Some lemmas

In what follows, we suppose that \(0 < p < 1\) (\(q < 0\)), \(\frac{1}{p} + \frac{1}{q} = 1\), \(\lambda \in (0,6]\), \(\alpha,\beta \in (0,1]\), \(\lambda _{1} \in (0,\frac{2}{\alpha } ] \cap (0,\lambda )\), \(\lambda _{2} \in (0,\frac{2}{\beta } ] \cap (0,\lambda )\),

$$\begin{aligned}& k_{\lambda } (\lambda _{i}): = B(\lambda _{i},\lambda - \lambda _{i})\quad (i = 1,2). \end{aligned}$$

\(a_{m},b_{n} \ge 0\) (\(m,n \in \mathrm{N} = \{ 1,2, \ldots \} \)) such that

$$ 0 < \sum_{m = 1}^{\infty } m^{p[1 - \alpha (\frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q})] - 1} a_{m}^{p} < \infty \quad \text{and}\quad 0 < \sum _{n = 1}^{\infty } n^{q[1 - \beta (\frac{\lambda - \lambda _{1}}{q} + \frac{\lambda _{2}}{p})] - 1} b_{n}^{q} < \infty . $$
(7)

Lemma 1

For \(\lambda _{2} \in (0,\frac{2}{\beta } ] \cap (0,\lambda )\) (\(\lambda _{1} \in (0,\lambda )\)), define the following weight coefficient:

$$ \varpi (\lambda _{2},m): = m^{\alpha (\lambda - \lambda _{2})}\sum _{n = 1}^{\infty } \frac{\beta n^{\beta \lambda _{2} - 1}}{(m^{\alpha } + n^{\beta } )^{\lambda }} \quad (m \in \mathrm{N}). $$
(8)

We have the following inequalities:

$$ 0 < k_{\lambda } (\lambda _{2}) \biggl(1 - O\biggl( \frac{1}{m^{\alpha \lambda _{2}}}\biggr)\biggr) < \varpi (\lambda _{2},m) < k_{\lambda } (\lambda _{2})\quad (m \in \mathrm{N}), $$
(9)

where \(O(\frac{1}{m^{\alpha \lambda _{2}}}): = \frac{1}{k_{\lambda } (\lambda _{2})}\int _{0}^{\frac{1}{m^{\alpha }}} \frac{u^{\lambda _{2} - 1}}{(1 + u)^{\lambda }}\,du > 0 \).

Proof

For fixed \(m \in \mathrm{N}\), we set the real function \(g(m,t)\) as follows:

$$ g(m,t): = \frac{\beta t^{\beta \lambda _{2} - 1}}{(m^{\alpha } + t^{\beta } )^{\lambda }} \quad (t > 0). $$

By means of the Euler–Maclaurin summation formula (cf. [2, 3]) and the Bernoulli function of 1-order \(P_{1}(t): = t - [t] - \frac{1}{2}\), we have

$$\begin{aligned}& \sum_{n = 1}^{\infty } g(m,n) = \int _{1}^{\infty } g(m,t)\,dt + \frac{1}{2} g(m,1) + \int _{1}^{\infty } P_{1}(t)g'(m,t) \,dt \\& \hphantom{\sum_{n = 1}^{\infty } g(m,n) }= \int _{0}^{\infty } g(m,t)\,dt - h(m), \\& h(m): = \int _{0}^{1} g(m,t)\,dt - \frac{1}{2}g(m,1) - \int _{1}^{\infty } P_{1}(t)g'(m,t) \,dt. \end{aligned}$$

We obtain \(- \frac{1}{2}g(m,1) = \frac{ - \beta }{2(m^{\alpha } + 1)^{\lambda }} \) and

$$\begin{aligned} - g'(m,t) &= - \frac{\beta (\beta \lambda _{2} - 1)t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda }} + \frac{\beta ^{2}\lambda t^{\beta + \beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda + 1}} \\ &= - \frac{\beta (\beta \lambda _{2} - 1)t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda }} + \frac{\beta ^{2}\lambda (m^{\alpha } + t^{\beta } - m^{\alpha } )t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda + 1}} \\ &= \frac{\beta (\beta \lambda - \beta \lambda _{2} + 1)t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda }} - \frac{\beta ^{2}\lambda m^{\alpha } t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda + 1}}. \end{aligned}$$

Integrating by parts, we have

$$\begin{aligned} \int _{0}^{1} g(m,t)\,dt =& \int _{0}^{1} \frac{\beta t^{\beta \lambda _{2} - 1}}{(m^{\alpha } + t^{\beta } )^{\lambda }}\,dt\stackrel{u = t^{\beta }}{=} \int _{0}^{1} \frac{u^{\lambda _{2} - 1}}{(m^{\alpha } + u)^{\lambda }}\,du \\ =& \frac{1}{\lambda _{2}} \int _{0}^{1} \frac{du^{\lambda _{2}}}{(m^{\alpha } + u)^{\lambda }} \\ =& \frac{1}{\lambda _{2}}\frac{u^{\lambda _{2}}}{(m^{\alpha } + u)^{\lambda }} |_{0}^{1} + \frac{\lambda }{\lambda _{2}} \int _{0}^{1} \frac{u^{\lambda _{2}}}{(m^{\alpha } + u)^{\lambda + 1}}\,du \\ =& \frac{1}{\lambda _{2}}\frac{1}{(m^{\alpha } + 1)^{\lambda }} + \frac{\lambda }{\lambda _{2}(\lambda _{2} + 1)} \int _{0}^{1} \frac{du^{\lambda _{2} + 1}}{(m^{\alpha } + u)^{\lambda + 1}} \\ >& \frac{1}{\lambda _{2}}\frac{1}{(m^{\alpha } + 1)^{\lambda }} + \frac{\lambda }{\lambda _{2}(\lambda _{2} + 1)}\biggl[ \frac{u^{\lambda _{2} + 1}}{(m^{\alpha } + u)^{\lambda + 1}}\biggr]_{0}^{1} \\ &{}+ \frac{\lambda (\lambda + 1)}{\lambda _{2}(\lambda _{2} + 1)(m^{\alpha } + 1)^{\lambda + 2}} \int _{0}^{1} u^{\lambda _{2} + 1}\,du \\ =& \frac{1}{\lambda _{2}}\frac{1}{(m^{\alpha } + 1)^{\lambda }} + \frac{\lambda }{\lambda _{2}(\lambda _{2} + 1)}\frac{1}{(m^{\alpha } + 1)^{\lambda + 1}} \\ &{}+ \frac{\lambda (\lambda + 1)}{\lambda _{2}(\lambda _{2} + 1)(\lambda _{2} + 2)}\frac{1}{(m^{\alpha } + 1)^{\lambda + 2}}. \end{aligned}$$

For \(0 < \lambda _{2} \le \frac{2}{\beta }\), \(0 < \beta \le 1\), \(\lambda _{2} < \lambda \le 6\), it follows that

$$ ( - 1)^{i}\frac{d^{i}}{dt^{i}}\biggl[\frac{t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda }} \biggr] > 0,( - 1)^{i}\frac{d^{i}}{dt^{i}}\biggl[\frac{t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda + 1}}\biggr] > 0\quad (i = 0,1,2,3). $$

Still using the Euler–Maclaurin summation formula (cf. [2]), we obtain

$$\begin{aligned}& \beta (\beta \lambda - \beta \lambda _{2} + 1) \int _{1}^{\infty } P_{1}(t)\frac{t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda }} \,dt > - \frac{\beta (\beta \lambda - \beta \lambda _{2} + 1)}{12(m^{\alpha } + 1)^{\lambda }}, \\& - \beta ^{2}m^{\alpha } \lambda \int _{1}^{\infty } P_{1}(t)\frac{t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda + 1}} \,dt \\& \quad > \frac{\beta ^{2}m^{\alpha } \lambda }{12(m^{\alpha } + 1)^{\lambda + 1}} - \frac{\beta ^{2}m^{\alpha } \lambda }{720}\biggl[\frac{t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda + 1}} \biggr]''_{t = 1} \\& \quad > \frac{\beta ^{2}(m^{\alpha } + 1 - 1)\lambda }{12(m^{\alpha } + 1)^{\lambda + 1}} - \frac{\beta ^{2}(m^{\alpha } + 1)\lambda }{720} \\& \qquad {}\times \biggl[\frac{(\lambda + 1)(\lambda + 2)\beta ^{2}}{(m^{\alpha } + 1)^{\lambda + 3}} + \frac{\beta (\lambda + 1)(5 - \beta - 2\beta \lambda _{2})}{(m^{\alpha } + 1)^{\lambda + 2}} + \frac{(2 - \beta \lambda _{2})(3 - \beta \lambda _{2})}{(m^{\alpha } + 1)^{\lambda + 1}}\biggr] \\& \quad = \frac{\beta ^{2}\lambda }{12(m^{\alpha } + 1)^{\lambda }} - \frac{\beta ^{2}\lambda }{12(m^{\alpha } + 1)^{\lambda + 1}} - \frac{\beta ^{2}\lambda }{720}\biggl[ \frac{(\lambda + 1)(\lambda + 2)\beta ^{2}}{(m^{\alpha } + 1)^{\lambda + 2}} \\& \qquad {}+ \frac{\beta (\lambda + 1)(5 - \beta - 2\beta \lambda _{2})}{(m^{\alpha } + 1)^{\lambda + 1}} + \frac{(2 - \beta \lambda _{2})(3 - \beta \lambda _{2})}{(m^{\alpha } + 1)^{\lambda }} \biggr], \end{aligned}$$

and then we have

$$\begin{aligned}& h(m) > \frac{1}{(m^{\alpha } + 1)^{\lambda }} h_{1} + \frac{\lambda }{(m^{\alpha } + 1)^{\lambda + 1}}h_{2} + \frac{\lambda (\lambda + 1)}{(m^{\alpha } + 1)^{\lambda + 2}}h_{3}, \\& h_{1}: = \frac{1}{\lambda _{2}} - \frac{\beta }{2} - \frac{\beta - \beta ^{2}\lambda _{2}}{12} - \frac{\beta ^{2}\lambda (2 - \beta \lambda _{2})(3 - \beta \lambda _{2})}{720}, \\& h_{2}: = \frac{1}{\lambda _{2}(\lambda _{2} + 1)} - \frac{\beta ^{2}}{12} - \frac{\beta ^{3}(\lambda + 1)(5 - \beta - 2\beta \lambda _{2})}{720},\quad \text{and} \\& h_{3}: = \frac{1}{\lambda _{2}(\lambda _{2} + 1)(\lambda _{2} + 2)} - \frac{\beta ^{4}(\lambda + 2)}{720}. \end{aligned}$$

We find that

$$ h_{1} \ge \frac{1}{\lambda _{2}} - \frac{\beta }{2} - \frac{\beta - \beta ^{2}\lambda _{2}}{12} - \frac{\lambda \beta ^{2}(2 - \beta \lambda _{2})(3 - \beta \lambda _{2})}{720} = \frac{g(\lambda _{2})}{720\lambda _{2}}, $$

where we indicate a real function \(g(\sigma )\) (\(\sigma \in (0,\frac{2}{\beta } ]\)) as follows:

$$ g(\sigma ): = 720 - \bigl(420\beta + 6\lambda \beta ^{2}\bigr)\sigma + \bigl(60\beta ^{2} + 5\lambda \beta ^{3}\bigr)\sigma ^{2} - \lambda \beta ^{4}\sigma ^{3}. $$

We obtain that, for \(\beta \in (0,1]\), \(\lambda \in (0,6]\) and \(\sigma \in (0,\frac{2}{\beta } ]\),

$$\begin{aligned} g'(\sigma ) =& - \bigl(420\beta + 6\lambda \beta ^{2} \bigr) + 2\bigl(60\beta ^{2} + 5\lambda \beta ^{3}\bigr) \sigma - 3\beta ^{4}\sigma ^{2} \\ \le& - 420\beta - 6\lambda \beta ^{2} + 2\bigl(60\beta ^{2} + 5\lambda \beta ^{3}\bigr)\frac{2}{\beta } \\ =& (14\lambda \beta - 180)\beta < 0, \end{aligned}$$

and then it follows that \(h_{1} \ge \frac{g(\lambda _{2})}{720\lambda _{2}} \ge \frac{g(2/\beta )}{720\lambda _{2}} = \frac{1}{6\lambda _{2}} > 0\). We also obtain that, for \(\lambda _{2} \in (0,\frac{2}{\beta } ]\),

$$\begin{aligned}& h_{2} > \frac{\beta ^{2}}{6} - \frac{\beta ^{2}}{12} - \frac{5(\lambda + 1)\beta ^{2}}{720} = \biggl(\frac{1}{12} - \frac{\lambda + 1}{140}\biggr)\beta ^{2} > 0 \quad (0 < \lambda \le 6),\quad \text{and} \\& h_{3} \ge \biggl(\frac{1}{24} - \frac{\lambda + 2}{720}\biggr)\beta ^{3} > 0(0 < \lambda \le 6). \end{aligned}$$

Hence, we have \(h(m) > 0\). Setting \(t = m^{\alpha /\beta } u^{1/\beta }\), it follows that

$$\begin{aligned} \varpi (\lambda _{2},m) =& m^{\alpha (\lambda - \lambda _{2})}\sum _{n = 1}^{\infty } g(m,n) < m^{\alpha (\lambda - \lambda _{2})} \int _{0}^{\infty } g(m,t)\,dt \\ =& m^{\alpha (\lambda - \lambda _{2})} \int _{0}^{\infty } \frac{\beta t^{\beta \lambda _{2} - 1}}{(m^{\alpha } + t^{\beta } )^{\lambda }}\,dt = \int _{0}^{\infty } \frac{u^{\lambda _{2} - 1}}{(1 + u)^{\lambda }}\,du = B(\lambda _{2},\lambda - \lambda _{2}). \end{aligned}$$

On the other hand, by using the Euler–Maclaurin summation formula, we also have

$$\begin{aligned}& \sum_{n = 1}^{\infty } g(m,n) = \int _{1}^{\infty } g(m,t)\,dt + \frac{1}{2} g(m,1) + \int _{1}^{\infty } P_{1}(t)g'(m,t) \,dt \\& \hphantom{\sum_{n = 1}^{\infty } g(m,n)}= \int _{1}^{\infty } g(m,t)\,dt + H(m), \\& H(m): = \frac{1}{2}g(m,1) + \int _{1}^{\infty } P_{1}(t)g'(m,t) \,dt. \end{aligned}$$

We have obtained that \(\frac{1}{2}g(m,1) = \frac{\beta }{2(m^{\alpha } + 1)^{\lambda }} \) and

$$ g'(m,t) = - \frac{\beta (\beta \lambda - \beta \lambda _{2} + 1)t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda }} + \frac{\beta ^{2}\lambda m^{\alpha } t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda + 1}}. $$

For \(\lambda _{2} \in (0,\frac{2}{\beta } ] \cap (0,\lambda )\), \(0 < \lambda \le 6\), by means of the Euler–Maclaurin summation formula, we obtain

$$\begin{aligned}& - \beta (\beta \lambda - \beta \lambda _{2} + 1) \int _{1}^{\infty } P_{1}(t)\frac{t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda }} \,dt > 0,\quad \text{and} \\& \beta ^{2}m^{\alpha } \lambda \int _{1}^{\infty } P_{1}(t)\frac{t^{\beta \lambda _{2} - 2}}{(m^{\alpha } + t^{\beta } )^{\lambda + 1}} \,dt > - \frac{\beta ^{2}m^{\alpha } \lambda }{12(m^{\alpha } + 1)^{\lambda + 1}} > - \frac{\beta ^{2}\lambda }{12(m^{\alpha } + 1)^{\lambda }}. \end{aligned}$$

Hence, we have

$$ H(m) > \frac{\beta }{2(m^{\alpha } + 1)^{\lambda }} - \frac{\beta ^{2}\lambda }{12(m^{\alpha } + 1)^{\lambda }} \ge \frac{\beta }{2(m^{\alpha } + 1)^{\lambda }} - \frac{6\beta }{12(m^{\alpha } + 1)^{\lambda }} = 0, $$

and then we obtain

$$\begin{aligned} \varpi (\lambda _{2},m) =& m^{\alpha (\lambda - \lambda _{2})}\sum _{n = 1}^{\infty } g(m,n) > m^{\alpha (\lambda - \lambda _{2})} \int _{1}^{\infty } g(m,t)\,dt \\ =& m^{\alpha (\lambda - \lambda _{2})} \int _{0}^{\infty } g(m,t)\,dt - m^{\alpha (\lambda - \lambda _{2})} \int _{0}^{1} g(m,t)\,dt \\ =& k_{\lambda } (\lambda _{2})\biggl[1 - \frac{1}{k_{\lambda } (\lambda _{2})} \int _{0}^{\frac{1}{m^{\alpha }}} \frac{u^{\lambda _{2} - 1}}{(1 + u)^{\lambda }}\,du \biggr] > 0, \end{aligned}$$

where we indicate \(O(\frac{1}{m^{\alpha \lambda _{2}}}) = \frac{1}{k_{\lambda } (\lambda _{2})}\int _{0}^{\frac{1}{m^{\alpha }}} \frac{u^{\lambda _{2} - 1}}{(1 + u)^{\lambda }}\,du > 0\),satisfying

$$ 0 < \int _{0}^{\frac{1}{m^{\alpha }}} \frac{u^{\lambda _{2} - 1}}{(1 + u)^{\lambda }}\,du < \int _{0}^{\frac{1}{m^{\alpha }}} u^{\lambda _{2} - 1}\,du = \frac{1}{\lambda _{2}m^{\alpha \lambda _{2}}}. $$

Therefore, we obtain inequalities (7).

The lemma is proved. □

Lemma 2

We have the following reverse Hardy–Hilbert inequality with the intermediate variables:

$$\begin{aligned}& I = \sum_{n = 1}^{\infty } \sum _{m = 1}^{\infty } \frac{a_{m}b_{n}}{(m^{\alpha } + n^{\beta } )^{\lambda }} > \biggl( \frac{1}{\beta } k_{\lambda } (\lambda _{2})\biggr)^{\frac{1}{p}} \biggl(\frac{1}{\alpha } k_{\lambda } (\lambda _{1}) \biggr)^{\frac{1}{q}} \\& \hphantom{I =}{}\times \Biggl\{ \sum_{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\alpha \lambda _{2}}}\biggr)\biggr)m^{p[1 - \alpha (\frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q})] - 1} a_{m}^{p}\Biggr\} ^{\frac{1}{p}} \\& \hphantom{I =}{}\times \Biggl\{ \sum _{n = 1}^{\infty } n^{q[1 - \beta (\frac{\lambda - \lambda _{1}}{q} + \frac{\lambda _{2}}{p})] - 1} b_{n}^{q} \Biggr\} ^{\frac{1}{q}}. \end{aligned}$$
(10)

Proof

In the same way, for \(\lambda _{1} \in (0,\frac{2}{\alpha } ] \cap (0,\lambda )\) (\(\lambda _{2} \in (0,\lambda )\)), \(n \in \mathbf{N}\), we obtain the following inequalities for the other weight coefficient:

$$ 0 < k_{\lambda } (\lambda _{1}) \biggl(1 - O\biggl( \frac{1}{n^{\beta \lambda _{1}}}\biggr)\biggr) < \omega (\lambda _{1},n): = n^{\beta (\lambda - \lambda _{1})}\sum_{m = 1}^{\infty } \frac{\alpha m^{\alpha \lambda _{1} - 1}}{(m^{\alpha } + n^{\beta } )^{\lambda }} < k_{\lambda } (\lambda _{1}), $$
(11)

where \(O(\frac{1}{n^{\beta \lambda _{1}}}): = \frac{1}{k_{\lambda } (\lambda _{1})}\int _{0}^{\frac{1}{n^{\beta }}} \frac{u^{\lambda _{1} - 1}}{(1 + u)^{\lambda }}\,du > 0 \).

By the reverse Hölder inequality (cf. [34]), we obtain

$$\begin{aligned} I =& \sum_{n = 1}^{\infty } \sum _{m = 1}^{\infty } \frac{1}{(m^{\alpha } + n^{\beta } )^{\lambda }} \biggl[ \frac{m^{\alpha (1 - \lambda {}_{1})/q}(\beta n^{\beta - 1})^{1/p}}{n^{\beta (1 - \lambda _{2})/p}(\alpha m^{\alpha - 1})^{1/q}}a_{m}\biggr] \biggl[\frac{n^{\beta (1 - \lambda _{2})/p}(\alpha m^{\alpha - 1})^{1/q}}{m^{\alpha (1 - \lambda {}_{1})/q}(\beta n^{\beta - 1})^{1/p}}b_{n} \biggr] \\ \ge& \Biggl[\frac{1}{\beta } \sum_{m = 1}^{\infty } \sum_{n = 1}^{\infty } \frac{\beta }{(m^{\alpha } + n^{\beta } )^{\lambda }} \frac{m^{\alpha (1 - \lambda {}_{1})(p - 1)}n^{\beta - 1}a_{m}^{p}}{n^{\beta (1 - \lambda _{2})}(\alpha m^{\alpha - 1})^{p - 1}}\Biggr]^{\frac{1}{p}} \\ &{}\times \Biggl[\frac{1}{\alpha } \sum_{n = 1}^{\infty } \sum_{m = 1}^{\infty } \frac{\alpha }{(m^{\alpha } + n^{\beta } )^{\lambda }} \frac{n^{\beta (1 - \lambda _{2})(q - 1)}m^{\alpha - 1}b_{n}^{q}}{m^{\alpha (1 - \lambda {}_{1})}(\beta n^{\beta - 1})^{q - 1}}\Biggr]^{\frac{1}{q}} \\ =& \frac{1}{\alpha ^{1/q}\beta ^{1/p}}\Biggl\{ \sum_{m = 1}^{\infty } \varpi (\lambda _{2},m) m^{p[1 - \alpha (\frac{\lambda - \lambda _{2}}{p} + \frac{\lambda {}_{1}}{q})] - 1}a_{m}^{p} \Biggr\} ^{\frac{1}{p}} \\ &{}\times \Biggl\{ \sum_{n = 1}^{\infty } \omega (\lambda {}_{1},n) n^{q[1 - \beta (\frac{\lambda - \lambda _{1}}{q} + \frac{\lambda _{2}}{p})] - 1}b_{n}^{q} \Biggr\} ^{\frac{1}{q}}. \end{aligned}$$

Then, by (9) and (11) (for \(0 < p < 1\) (\(q < 0\))), we have (10).

The lemma is proved. □

Remark 1

By (10), for \(\lambda _{1} + \lambda _{2} = \lambda \in (0,6]\), \(K_{\lambda } (\lambda _{1}): = \frac{1}{\alpha ^{1/q}\beta ^{1/p}}B(\lambda _{1},\lambda _{2})\), we find

$$\begin{aligned}& \omega (\lambda _{1},n) = n^{\beta \lambda _{2}}\sum _{m = 1}^{\infty } \frac{\alpha m^{\alpha \lambda _{1} - 1}}{(m^{\alpha } + n^{\beta } )^{\lambda }}, \\& 0 < \sum_{m = 1}^{\infty } m^{p(1 - \alpha \lambda _{1}) - 1} a_{m}^{p} < \infty ,\qquad 0 < \sum _{n = 1}^{\infty } n^{q(1 - \beta \lambda _{2}) - 1} b_{n}^{q} < \infty , \end{aligned}$$
(12)

and the following inequality:

$$\begin{aligned}& \sum_{n = 1}^{\infty } \sum _{m = 1}^{\infty } \frac{a_{m}b_{n}}{(m^{\alpha } + n^{\beta } )^{\lambda }} \\& \quad > K_{\lambda } (\lambda _{1}) \Biggl[\sum _{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\alpha \lambda _{2}}} \biggr)\biggr)m^{p(1 - \alpha \lambda _{1}) - 1} a_{m}^{p}\Biggr]^{\frac{1}{p}} \Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \beta \lambda _{2}) - 1} b_{n}^{q}\Biggr]^{\frac{1}{q}}. \end{aligned}$$
(13)

Lemma 3

The constant factor \(K_{\lambda } (\lambda _{1})\) in (13) is the best possible.

Proof

For any \(0 < \varepsilon < p\lambda _{1}\), we set

$$ \tilde{a}_{m}: = m^{\alpha (\lambda _{1} - \frac{\varepsilon }{p}) - 1},\qquad \tilde{b}_{n}: = n^{\beta (\lambda _{2} - \frac{\varepsilon }{q}) - 1}\quad (m,n \in \mathrm{N}). $$

If there exists a constant \(M \ge K_{\lambda } (\lambda _{1})\) such that (13) is valid when we replace \(K_{\lambda } (\lambda _{1})\) with M, then in particular, by substitution of \(a_{m} = \tilde{a}_{m}\) and \(b_{n} = \tilde{b}_{n}\) in (13), we have

$$\begin{aligned} \tilde{I} : =& \sum_{n = 1}^{\infty } \sum _{m = 1}^{\infty } \frac{\tilde{a}_{m}\tilde{b}_{n}}{(m^{\alpha } + n^{\beta } ) ^{\lambda }} \\ >& M\Biggl[\sum _{m = 1}^{\infty } \biggl(1 - O\biggl( \frac{1}{m^{\alpha \lambda _{2}}}\biggr)\biggr)m^{p(1 - \alpha \lambda _{1}) - 1} \tilde{a}_{m}^{p} \Biggr]^{\frac{1}{p}}\Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \beta \lambda _{2}) - 1} \tilde{b}_{n}^{q}\Biggr]^{\frac{1}{q}}. \end{aligned}$$

In the following, we show that \(M \le K_{\lambda } (\lambda _{1})\),from which it follows that \(M = K_{\lambda } (\lambda _{1})\) is the best possible constant factor of (13). By the decreasingness property of series, we obtain

$$\begin{aligned} \tilde{I} >& M\Biggl[\sum_{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\alpha \lambda _{2}}}\biggr)\biggr)m^{p(1 - \alpha \lambda _{1}) - 1} m^{p\alpha \lambda _{1} - \alpha \varepsilon - p}\Biggr]^{\frac{1}{p}}\Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \beta \lambda _{2}) - 1} n^{q\beta \lambda _{2} - \beta \varepsilon - q}\Biggr]^{\frac{1}{q}} \\ =& M\Biggl[\sum_{m = 1}^{\infty } m^{ - \alpha \varepsilon - 1} - \sum_{m = 1}^{\infty } O \bigl(m^{ - \alpha (\lambda _{2} + \varepsilon ) - 1}\bigr) \Biggr]^{\frac{1}{p}}\Biggl(1 + \sum _{n = 2}^{\infty } n^{ - \beta \varepsilon - 1} \Biggr)^{\frac{1}{q}} \\ >& M\biggl( \int _{1}^{\infty } x^{ - \alpha \varepsilon - 1}\,dx - O(1) \biggr)^{\frac{1}{p}}\biggl(1 + \int _{1}^{\infty } y^{ - \beta \varepsilon - 1}\,dy \biggr)^{\frac{1}{q}} \\ =& \frac{M}{\varepsilon } \biggl(\frac{1}{\alpha } - \varepsilon O(1) \biggr)^{\frac{1}{p}}\biggl(\varepsilon + \frac{1}{\beta } \biggr)^{\frac{1}{q}}. \end{aligned}$$

By (12), setting \(\hat{\lambda }_{1} = \lambda _{1} - \frac{\varepsilon }{p} \in (0,\frac{2}{\alpha } ) \cap (0,\lambda )\) (\(0 < \hat{\lambda }_{2} = \lambda _{2} + \frac{\varepsilon }{p} = \lambda - \hat{\lambda }_{1} < \lambda \)), we find

$$\begin{aligned} \tilde{I} =& \sum_{n = 1}^{\infty } \Biggl[n^{\beta \hat{\lambda }_{2}}\sum_{m = 1}^{\infty } \frac{1}{(m^{\alpha } + n^{\beta } )^{\lambda }} m^{\alpha \hat{\lambda }_{1} - 1}\Biggr]n^{ - \beta \varepsilon - 1} \\ =& \frac{1}{\alpha } \sum_{n = 1}^{\infty } \omega (\hat{\lambda }_{1},n)n^{ - \beta \varepsilon - 1} < \frac{1}{\alpha } k_{\lambda } (\hat{\lambda }_{1})\sum_{n = 1}^{\infty } n^{ - \beta \varepsilon - 1} \\ =& \frac{1}{\alpha } k_{\lambda } (\hat{\lambda }_{1}) \Biggl(1 + \sum_{n = 2}^{\infty } n^{ - \beta \varepsilon - 1}\Biggr) < \frac{1}{\alpha } k_{\lambda } (\hat{\lambda }_{1}) \biggl(1 + \int _{1}^{\infty } x^{ - \beta \varepsilon - 1}\,dx\biggr) \\ =& \frac{1}{\varepsilon \alpha \beta } k_{\lambda } (\hat{\lambda }_{1}) ( \varepsilon \beta + 1). \end{aligned}$$

By virtue of the above results, we have

$$ \frac{1}{\alpha \beta } B\biggl(\lambda _{1} - \frac{\varepsilon }{p}, \lambda _{2} + \frac{\varepsilon }{p}\biggr) (\varepsilon \beta + 1) > \varepsilon \tilde{I} > M \biggl(\frac{1}{\alpha } - \varepsilon O(1) \biggr)^{\frac{1}{p}}\biggl(\varepsilon + \frac{1}{\beta } \biggr)^{\frac{1}{q}}. $$

For \(\varepsilon \to 0^{ +} \), in view of the continuity of the beta function, it follows that

$$ K_{\lambda } (\lambda _{1}) = \frac{1}{\alpha ^{1/q}\beta ^{1/p}}B(\lambda _{1},\lambda _{2})\ge M. $$

Hence, \(M = K_{\lambda } (\lambda _{1})\) is the best possible constant factor of (13).

The lemma is proved. □

Remark 2

Setting \(\tilde{\lambda }_{1}: = \frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q}\), \(\tilde{\lambda }_{2}: = \frac{\lambda - \lambda _{1}}{q} + \frac{\lambda _{2}}{p}\) in (10), we find

$$\begin{aligned}& \tilde{\lambda }_{1} + \tilde{\lambda }_{2} = \frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q} + \frac{\lambda - \lambda _{1}}{q} + \frac{\lambda _{2}}{p} = \frac{\lambda }{p} + \frac{\lambda }{q} = \lambda ,\quad \text{and} \\& I = \sum_{n = 1}^{\infty } \sum _{m = 1}^{\infty } \frac{a_{m}b_{n}}{(m^{\alpha } + n^{\beta } )^{\lambda }} > \biggl( \frac{1}{\beta } k_{\lambda } (\lambda _{2})\biggr)^{\frac{1}{p}} \biggl(\frac{1}{\alpha } k_{\lambda } (\lambda _{1}) \biggr)^{\frac{1}{q}} \\& \hphantom{I =}{}\times \Biggl[\sum_{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\alpha \lambda _{2}}}\biggr)\biggr)m^{p(1 - \alpha \tilde{\lambda }_{1}) - 1} a_{m}^{p}\Biggr]^{\frac{1}{p}}\Biggl[\sum _{n = 1}^{\infty } n^{q(1 - \beta \tilde{\lambda }_{2}) - 1} b_{n}^{q} \Biggr]^{\frac{1}{q}}. \end{aligned}$$
(14)
  1. (i)

    For \(\lambda - \lambda _{1} - \lambda _{2} \in ( - \lambda _{1}p,(\lambda - \lambda _{1})p)\), we have

    $$ 0 < \tilde{\lambda }_{1} = \frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q} < \lambda ,\quad 0 < \tilde{\lambda }_{2} = \lambda - \tilde{\lambda }_{1} < \lambda ; $$
  2. (ii)

    For \(\lambda - \lambda _{1} - \lambda _{2} \in [(\lambda - \lambda _{1} - \frac{2}{\beta } )p,(\frac{2}{\alpha } - \lambda _{1})p]\) (\(\lambda \le \min \{ 6,\frac{2}{\alpha } + \frac{2}{\beta } \} \)), we have

    $$ \tilde{\lambda }_{1} \le \frac{2}{\alpha },\qquad \tilde{\lambda }_{2} \le \frac{2}{\beta }. $$

In view of (i) and (ii), we can rewrite (10) as follows:

$$\begin{aligned}& \sum_{n = 1}^{\infty } \sum _{m = 1}^{\infty } \frac{a_{m}b_{n}}{(m^{\alpha } + n^{\beta } )^{\lambda }} \\& \quad > K_{\lambda } (\lambda _{1}) \Biggl[\sum _{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\alpha \tilde{\lambda }_{2}}} \biggr)\biggr)m^{p(1 - \alpha \tilde{\lambda }_{1}) - 1} a_{m}^{p}\Biggr]^{\frac{1}{p}} \Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \beta \tilde{\lambda }_{2}) - 1} b_{n}^{q}\Biggr]^{\frac{1}{q}}. \end{aligned}$$
(15)

Lemma 4

If the constant factor \((\frac{1}{\beta } k_{\lambda } (\lambda _{2}))^{\frac{1}{p}}(\frac{1}{\alpha } k_{\lambda } (\lambda _{1}))^{\frac{1}{q}}\) in (10) (or (14)) is the best possible, then for \(0 < \lambda \le \min \{ 6,\frac{2}{\alpha } + \frac{2}{\beta } \}\) and

$$ \lambda - \lambda _{1} - \lambda _{2} \in \bigl( - \lambda _{1}p,(\lambda - \lambda _{1})p\bigr)\cap \biggl[\biggl( \lambda - \lambda _{1} - \frac{2}{\beta } \biggr)p,\biggl( \frac{2}{\alpha } - \lambda _{1}\biggr)p\biggr]\bigl( \supset \{ 0\} \bigr), $$
(16)

we have \(\lambda _{1} + \lambda _{2} = \lambda \).

Proof

If the constant factor \((\frac{1}{\beta } k_{\lambda } (\lambda _{2}))^{\frac{1}{p}}(\frac{1}{\alpha } k_{\lambda } (\lambda _{1}))^{\frac{1}{q}}\) in (10) (or (14)) is the best possible, then in view of (16) and (15), we have the following inequality:

$$ \biggl(\frac{1}{\beta } k_{\lambda } (\lambda _{2}) \biggr)^{\frac{1}{p}}\biggl(\frac{1}{\alpha } k_{\lambda } (\lambda _{1})\biggr)^{\frac{1}{q}}\ge K_{\lambda } (\tilde{\lambda }_{1}) = \frac{1}{\beta ^{1/p}\alpha ^{1/q}}k_{\lambda } (\tilde{\lambda }_{1}), $$

namely, \(k_{\lambda }^{\frac{1}{p}}(\lambda _{2})k_{\lambda }^{\frac{1}{q}}(\lambda _{1})\ge k_{\lambda } (\tilde{\lambda }_{1})\).

By the reverse Hölder inequality (cf. [34]), we obtain

$$\begin{aligned} k_{\lambda } (\tilde{\lambda }_{1}) =& k_{\lambda } \biggl( \frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q}\biggr) \\ =& \int _{0}^{\infty } \frac{1}{(1 + u)^{\lambda }} u^{\frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q} - 1} \,du = \int _{0}^{\infty } \frac{1}{(1 + u)^{\lambda }} \bigl(u^{\frac{\lambda - \lambda _{2} - 1}{p}}\bigr) \bigl(u^{\frac{\lambda _{1} - 1}{q}}\bigr)\,du \\ \ge& \biggl[ \int _{0}^{\infty } \frac{1}{(1 + u)^{\lambda }} u^{\lambda - \lambda _{2} - 1} \,du\biggr]^{\frac{1}{p}}\biggl[ \int _{0}^{\infty } \frac{1}{(1 + u)^{\lambda }} u^{\lambda _{1} - 1} \,du\biggr]^{\frac{1}{q}} \\ = &\biggl[ \int _{0}^{\infty } \frac{1}{(1 + v)^{\lambda }} v^{\lambda _{2} - 1} \,dv\biggr]^{\frac{1}{p}}\biggl[ \int _{0}^{\infty } \frac{1}{(1 + u)^{\lambda }} u^{\lambda _{1} - 1} \,du\biggr]^{\frac{1}{q}} \\ =& k_{\lambda }^{\frac{1}{p}}(\lambda _{2})k_{\lambda }^{\frac{1}{q}}( \lambda _{1}). \end{aligned}$$
(17)

Hence, we have \(k_{\lambda }^{\frac{1}{p}}(\lambda _{2})k_{\lambda }^{\frac{1}{q}}(\lambda _{1}) = k_{\lambda } (\tilde{\lambda }_{1})\), from which it follows that (17) keeps the form of equality.

We observe that (17) keeps the form of equality if and only if there exist constants A and B such that they are not both zero and (cf. [34])

$$ Au^{\lambda - \lambda _{2} - 1} = Bu^{\lambda _{1} - 1}\quad \text{a.e. in } \mathrm{R}_{ +}. $$

Assuming that \(A \ne 0\), we have \(u^{\lambda - \lambda _{2} - \lambda _{1}} = \frac{B}{A}\) a.e. in \(\mathrm{R}_{ +}\), and then \(\lambda - \lambda _{2} - \lambda _{1} = 0\). Hence, we have \(\lambda _{1} + \lambda _{2} = \lambda \).

The lemma is proved. □

Main results

Theorem 1

Inequality (14) is equivalent to the following inequalities:

$$\begin{aligned}& J: = \Biggl\{ \sum_{n = 1}^{\infty } n^{p\beta \tilde{\lambda }_{2} - 1}\Biggl[\sum_{m = 1}^{\infty } \frac{1}{(m^{\alpha } + n^{\beta } )^{\lambda }} a_{m} \Biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\& \hphantom{J}> \biggl(\frac{1}{\beta } k_{\lambda } (\lambda _{2})\biggr)^{\frac{1}{p}}\biggl(\frac{1}{\alpha } k_{\lambda } ( \lambda _{1})\biggr)^{\frac{1}{q}}\Biggl[\sum _{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\alpha \lambda _{2}}} \biggr)\biggr)m^{p(1 - \alpha \tilde{\lambda }_{1}) - 1} a_{m}^{p} \Biggr]^{\frac{1}{p}}, \end{aligned}$$
(18)
$$\begin{aligned}& J_{1}: = \Biggl\{ \sum_{m = 1}^{\infty } \frac{m^{q\alpha \tilde{\lambda }_{1} - 1}}{(1 - O(\frac{1}{m^{\alpha \lambda _{2}}}))^{q - 1}}\Biggl[\sum_{n = 1}^{\infty } \frac{1}{(m^{\alpha } + n^{\beta } )^{\lambda }} b_{n} \Biggr]^{q}\Biggr\} ^{\frac{1}{q}} \\& \hphantom{J_{1}}> \biggl(\frac{1}{\beta } k_{\lambda } (\lambda _{2})\biggr)^{\frac{1}{p}}\biggl(\frac{1}{\alpha } k_{\lambda } ( \lambda _{1})\biggr)^{\frac{1}{q}}\Biggl[\sum _{n = 1}^{\infty } n^{q(1 - \beta \tilde{\lambda }_{2}) - 1} b_{n}^{q} \Biggr]^{\frac{1}{q}}. \end{aligned}$$
(19)

If the constant factor in (14) is the best possible, then so is the same constant factor in (18) and (19).

Proof

Suppose that (18) is valid. By the reverse Hölder inequality (cf. [34]), we have

$$ I = \sum_{n = 1}^{\infty } \Biggl[n^{\frac{ - 1}{p} + \beta \tilde{\lambda }_{2}} \sum_{m = 1}^{\infty } \frac{1}{(m^{\alpha } + n^{\beta } )^{\lambda }} a_{m} \Biggr]\bigl(n^{\frac{1}{p} - \beta \tilde{\lambda }_{2}}b_{n}\bigr)\ge J\Biggl[ \sum_{n = 1}^{\infty } n^{q(1 - \beta \tilde{\lambda }_{2}) - 1} b_{n}^{q}\Biggr]^{\frac{1}{q}}. $$
(20)

Then, by (18), we obtain (14). On the other hand, assuming that (14) is valid, we set

$$ b_{n}: = n^{p\beta \tilde{\lambda }_{2} - 1}\Biggl[\sum_{m = 1}^{\infty } \frac{1}{(m^{\alpha } + n^{\beta } )^{\lambda }} a_{m} \Biggr]^{p - 1},\quad n \in \mathbf{N}. $$

If \(J = \infty \), then (18) is naturally valid; if \(J = 0\), then it is impossible that makes (18) valid, namely, \(J > 0\). Suppose that \(0 < J < \infty \). By (14), we have

$$\begin{aligned}& 0 > \sum_{n = 1}^{\infty } n^{q(1 - \beta \tilde{\lambda }_{2}) - 1} b_{n}^{q} = J^{p} = I > \biggl(\frac{1}{\beta } k_{\lambda } (\lambda _{2})\biggr)^{\frac{1}{p}}\biggl( \frac{1}{\alpha } k_{\lambda } (\lambda _{1})\biggr)^{\frac{1}{q}} \\& \hphantom{0 >}{}\times \Biggl[\sum_{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\alpha \lambda _{2}}}\biggr)\biggr)m^{p(1 - \alpha \tilde{\lambda }_{1}) - 1} a_{m}^{p}\Biggr]^{\frac{1}{p}}J^{p - 1} > 0, \\& J = \Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \beta \tilde{\lambda }_{2}) - 1} b_{n}^{q}\Biggr]^{\frac{1}{p}} > \biggl(\frac{1}{\beta } k_{\lambda } (\lambda _{2})\biggr)^{\frac{1}{p}}\biggl( \frac{1}{\alpha } k_{\lambda } (\lambda _{1})\biggr)^{\frac{1}{q}} \\& \hphantom{J =}{}\times \Biggl[\sum_{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\alpha \lambda _{2}}}\biggr)\biggr)m^{p(1 - \alpha \tilde{\lambda }_{1}) - 1} a_{m}^{p}\Biggr]^{\frac{1}{p}}, \end{aligned}$$

namely, (18) follows, which is equivalent to (14).

Suppose that (19) is valid. By the reverse Hölder inequality (cf. [34]), we have

$$\begin{aligned}& I = \sum_{m = 1}^{\infty } \biggl[\biggl(1 - O \biggl(\frac{1}{m^{\alpha \lambda _{2}}}\biggr)\biggr)^{\frac{1}{p}}m^{\frac{1}{q} - \alpha \tilde{\lambda }_{1}}a_{m} \biggr] \Biggl[\frac{m^{\frac{ - 1}{q} + \alpha \tilde{\lambda }_{1}}}{(1 - O(\frac{1}{m^{\alpha \lambda _{2}}}))^{1/p}}\sum_{n = 1}^{\infty } \frac{1}{(m^{\alpha } + n^{\beta } ){}^{\lambda }} b_{n} \Biggr] \\& \hphantom{I}\ge \Biggl[\sum_{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\alpha \lambda _{2}}}\biggr)\biggr)m^{p(1 - \alpha \stackrel{\leftrightarrow }{\lambda }_{1}) - 1} a_{m}^{p}\Biggr]^{\frac{1}{p}}J_{1}. \end{aligned}$$
(21)

Then, by (19), we obtain (14). On the other hand, assuming that (14) is valid, we set

$$ a_{m}: = \frac{m^{q\alpha \tilde{\lambda }_{1} - 1}}{(1 - O(\frac{1}{m^{\alpha \lambda _{2}}}))^{q - 1}}\Biggl[\sum_{n = 1}^{\infty } \frac{1}{(m^{\alpha } + n^{\beta } )^{\lambda }} b_{n} \Biggr]^{q - 1},\quad m \in \mathrm{N}. $$

If \(J_{1} = \infty \), then (19) is naturally valid; if \(J_{1} = 0\), then it is impossible that makes (19) valid, namely, \(J_{1} > 0\). Suppose that \(0 < J_{1} < \infty \). By (14), we have

$$\begin{aligned}& \infty > \sum_{m = 1}^{\infty } \biggl(1 - O \biggl(\frac{1}{m^{\alpha \lambda _{2}}}\biggr)\biggr)m^{p(1 - \alpha \tilde{\lambda }_{1}) - 1} a_{m}^{p} = J_{1}^{q} = I \\& \hphantom{\infty}> \biggl(\frac{1}{\beta } k_{\lambda } (\lambda _{2})\biggr)^{\frac{1}{p}}\biggl(\frac{1}{\alpha } k_{\lambda } ( \lambda _{1})\biggr)^{\frac{1}{q}}J_{1}^{q - 1} \Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \beta \tilde{\lambda }_{2}) - 1} b_{n}^{q}\Biggr]^{\frac{1}{q}} > 0, \\& J_{1} = \Biggl[\sum_{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\alpha \lambda _{2}}}\biggr)\biggr)m^{p(1 - \alpha \tilde{\lambda }_{1}) - 1} a_{m}^{p}\Biggr]^{\frac{1}{q}} \\& \hphantom{J_{1}}> \biggl(\frac{1}{\beta } k_{\lambda } (\lambda _{2})\biggr)^{\frac{1}{p}}\biggl(\frac{1}{\alpha } k_{\lambda } ( \lambda _{1})\biggr)^{\frac{1}{q}}\Biggl[\sum _{n = 1}^{\infty } n^{q(1 - \beta \tilde{\lambda }_{2}) - 1} b_{n}^{q} \Biggr]^{\frac{1}{q}}, \end{aligned}$$

namely, (19) follows, which is equivalent to (14).

Hence, inequalities (14), (18), and (19) are equivalent.

If the constant factor in (14) is the best possible, then so is the constant factor in (18) and (19). Otherwise, by (20) (or (21)), we would reach a contradiction that the constant factor in (14) is not the best possible.

The theorem is proved. □

Theorem 2

The following statements (i), (ii), (iii), and (iv) are equivalent:

  1. (i)

    Both \(k_{\lambda }^{\frac{1}{p}}(\lambda _{2})k_{\lambda }^{\frac{1}{q}}(\lambda _{1})\) and \(k_{\lambda } (\frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q})\) are independent of p, q;

  2. (ii)

    \(k_{\lambda }^{\frac{1}{p}}(\lambda _{2})k_{\lambda }^{\frac{1}{q}}(\lambda _{1})\) is expressible as the following single integral:

    $$ k_{\lambda } \biggl(\frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q}\biggr) = k_{\lambda } (\tilde{\lambda }_{1}) = \int _{0}^{\infty } \frac{1}{(1 + u)^{\lambda }} u^{\tilde{\lambda }_{1} - 1} \,du; $$
  3. (iii)

    \((\frac{1}{\beta } k_{\lambda } (\lambda _{2}))^{\frac{1}{p}}(\frac{1}{\alpha } k_{\lambda } (\lambda _{1}))^{\frac{1}{q}}\) in (14) is the best possible constant factor;

  4. (iv)

    If \(0 < \lambda \le \min \{ 6,\frac{2}{\alpha } + \frac{2}{\beta } \}\) and

    $$\begin{aligned}& \lambda - \lambda _{1} - \lambda _{2} \in \bigl( - \lambda _{1}p,(\lambda - \lambda _{1})p\bigr)\cap \biggl[\biggl( \lambda - \lambda _{1} - \frac{2}{\beta } \biggr)p,\biggl( \frac{2}{\alpha } - \lambda _{1}\biggr)p\biggr], \end{aligned}$$

then we have \(\lambda _{1} + \lambda _{2} = \lambda \).

If statement (iv) follows, namely, \(\lambda _{1} + \lambda _{2} = \lambda \), then we have (13) and the following equivalent inequalities with the best possible constant factor \(K_{\lambda } (\lambda _{1})\):

$$\begin{aligned}& \Biggl\{ \sum_{n = 1}^{\infty } n^{p\beta \lambda _{2} - 1} \Biggl[\sum_{m = 1}^{\infty } \frac{1}{(m^{\alpha } + n^{\beta } )^{\lambda }} a_{m} \Biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\& \quad > K_{\lambda } (\lambda _{1})\Biggl[\sum _{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\alpha \lambda _{2}}} \biggr)\biggr)m^{p(1 - \alpha \lambda _{1}) - 1} a_{m}^{p}\Biggr]^{\frac{1}{p}}, \end{aligned}$$
(22)
$$\begin{aligned}& \Biggl\{ \sum_{m = 1}^{\infty } \frac{m^{q\alpha \lambda _{1} - 1}}{(1 - O(\frac{1}{m^{\alpha \lambda _{2}}}))^{q - 1}}\Biggl[\sum_{n = 1}^{\infty } \frac{1}{(m^{\alpha } + n^{\beta } )^{\lambda }} b_{n} \Biggr]^{q}\Biggr\} ^{\frac{1}{q}} > K_{\lambda } (\lambda _{1})\Biggl[\sum _{n = 1}^{\infty } n^{q(1 - \beta \lambda _{2}) - 1} b_{n}^{q} \Biggr]^{\frac{1}{q}}. \end{aligned}$$
(23)

Proof

(i) (ii). By (i), in view of the continuity of the beta function, we have

$$\begin{aligned}& k_{\lambda }^{\frac{1}{p}}(\lambda _{2})k_{\lambda }^{\frac{1}{q}}( \lambda _{1}) = \lim_{q \to - \infty } \lim_{p \to 1^{ -}} k_{\lambda }^{\frac{1}{p}}(\lambda _{2})k_{\lambda }^{\frac{1}{q}}( \lambda _{1}) = k_{\lambda } (\lambda _{2}), \\& k_{\lambda } \biggl(\frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q}\biggr) = \lim _{q \to - \infty } \lim_{p \to 1^{ -}} k_{\lambda } \biggl( \frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q}\biggr) = k_{\lambda } (\lambda - \lambda _{2}) = k_{\lambda } (\lambda _{2}), \end{aligned}$$

namely, \(k_{\lambda }^{\frac{1}{p}}(\lambda _{2})k_{\lambda }^{\frac{1}{q}}(\lambda _{1})\) is expressible as the following single integral:

$$ k_{\lambda } \biggl(\frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q}\biggr) = k_{\lambda } (\tilde{\lambda }_{1}) = \int _{0}^{\infty } \frac{1}{(1 + u)^{\lambda }} u^{\tilde{\lambda }_{1} - 1} \,du. $$

(ii) (iv). If \(k_{\lambda }^{\frac{1}{p}}(\lambda _{2})k_{\lambda }^{\frac{1}{q}}(\lambda _{1})=k_{\lambda } (\tilde{\lambda }_{1})\), then (17) keeps the form of equality. In view of the proof of Lemma 4, it follows that \(\lambda _{1} + \lambda _{2} = \lambda \).

(iv) (i). If \(\lambda _{1} + \lambda _{2} = \lambda \), then both \(k_{\lambda }^{\frac{1}{p}}(\lambda _{2})k_{\lambda }^{\frac{1}{q}}(\lambda _{1})\) and \(k_{\lambda } (\frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q})\) are equal to \(k_{\lambda } (\lambda _{1})\), which is independent of p, q. Hence, it follows that (i) (ii) (iv).

(iii) (iv). By the assumption and Lemma 4, we have \(\lambda _{1} + \lambda _{2} = \lambda \).

(iv) (iii). By Lemma 3, for \(\lambda = \lambda _{1} + \lambda _{2}\),

$$ \biggl(\frac{1}{\beta } k_{\lambda } (\lambda _{2}) \biggr)^{\frac{1}{p}}\biggl(\frac{1}{\alpha } k_{\lambda } (\lambda _{1})\biggr)^{\frac{1}{q}}\bigl( = K_{\lambda } (\lambda _{1})\bigr) $$

is the best possible constant factor of (14). Therefore, we have (iii) (iv).

Hence, statements (i), (ii), (iii), and (iv) are equivalent.

The theorem is proved. □

Remark 3

(i) For \(\alpha = \beta = 1\), \(\lambda _{1},\lambda _{2} \in (0,2]\) (\(\lambda _{1} + \lambda _{2} = \lambda \in (0,4]\)) in (13), (22), and (23), we have the following equivalent inequalities with the best possible constant factor \(B(\lambda _{1},\lambda _{2})\):

$$\begin{aligned}& \sum_{m = 1}^{\infty } \sum _{n = 1}^{\infty } \frac{a_{m}b_{n}}{(m + n)^{\lambda }} \\& \quad > B(\lambda _{1},\lambda _{2})\Biggl[\sum _{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\lambda _{2}}} \biggr)\biggr)m^{p(1 - \lambda _{1}) - 1}a_{m}^{p} \Biggr]^{\frac{1}{p}}\Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \lambda _{2}) - 1}b_{n}^{q} \Biggr]^{\frac{1}{q}}, \end{aligned}$$
(24)
$$\begin{aligned}& \Biggl\{ \sum_{n = 1}^{\infty } n^{p\lambda _{2} - 1} \Biggl[\sum_{m = 1}^{\infty } \frac{1}{(m + n)^{\lambda }} a_{m} \Biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\& \quad > B(\lambda _{1},\lambda _{2})\Biggl[\sum_{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\lambda _{2}}}\biggr)\biggr)m^{p(1 - \lambda _{1}) - 1} a_{m}^{p}\Biggr]^{\frac{1}{p}}, \end{aligned}$$
(25)
$$\begin{aligned}& \Biggl\{ \sum_{m = 1}^{\infty } \frac{m^{q\lambda _{1} - 1}}{(1 - O(\frac{1}{m^{\lambda _{2}}}))^{q - 1}}\Biggl[\sum_{n = 1}^{\infty } \frac{1}{(m + n)^{\lambda }} b_{n} \Biggr]^{q}\Biggr\} ^{\frac{1}{q}} > K_{\lambda } (\lambda _{1})\Biggl[\sum _{n = 1}^{\infty } n^{q(1 - \lambda _{2}) - 1} b_{n}^{q} \Biggr]^{\frac{1}{q}}. \end{aligned}$$
(26)

Inequality (24) is the reverse of (2) (cf. [33]).

(ii) For \(\alpha = \beta = \frac{1}{2}\), \(\lambda _{1},\lambda _{2} \in (0,4]\) (\(\lambda _{1} + \lambda _{2} = \lambda \in (0,6]\)) in (13), (22), and (23), we have the following equivalent inequalities with the best possible constant factor \(2B(\lambda _{1},\lambda _{2})\):

$$\begin{aligned}& \sum_{n = 1}^{\infty } \sum _{m = 1}^{\infty } \frac{a_{m}b_{n}}{(\sqrt{m} + \sqrt{n} )^{\lambda }} \\& \quad > 2B(\lambda _{1},\lambda _{2}) \Biggl[\sum _{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\lambda _{2}/2}} \biggr)\biggr)m^{p(1 - \frac{\lambda _{1}}{2}) - 1} a_{m}^{p} \Biggr]^{\frac{1}{p}}\Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \frac{\lambda _{2}}{2}) - 1} b_{n}^{q}\Biggr]^{\frac{1}{q}}, \end{aligned}$$
(27)
$$\begin{aligned}& \Biggl\{ \sum_{n = 1}^{\infty } n^{\frac{p\lambda _{2}}{2} - 1} \Biggl[\sum_{m = 1}^{\infty } \frac{1}{(\sqrt{m} + \sqrt{n} )^{\lambda }} a_{m} \Biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\& \quad > 2B(\lambda _{1},\lambda _{2})\Biggl[\sum _{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{\lambda _{2}/2}} \biggr)\biggr)m^{p(1 - \frac{\lambda _{1}}{2}) - 1} a_{m}^{p} \Biggr]^{\frac{1}{p}}, \end{aligned}$$
(28)
$$\begin{aligned}& \Biggl\{ \sum_{m = 1}^{\infty } \frac{m^{q\lambda _{1}/2 - 1}}{(1 - O(\frac{1}{m^{\lambda _{2}/2}}))^{q - 1}}\Biggl[\sum_{n = 1}^{\infty } \frac{1}{(\sqrt{m} + \sqrt{n} )^{\lambda }} b_{n} \Biggr]^{q}\Biggr\} ^{\frac{1}{q}} \\& \quad > 2B(\lambda _{1},\lambda _{2})\Biggl[\sum _{n = 1}^{\infty } n^{q(1 - \frac{\lambda _{2}}{2}) - 1} b_{n}^{q} \Biggr]^{\frac{1}{q}}. \end{aligned}$$
(29)

(iii) For \(\alpha = \beta = \frac{2}{3}\), \(\lambda _{1},\lambda _{2} \in (0,3]\) (\(\lambda _{1} + \lambda _{2} = \lambda \in (0,6]\)) in (13), (22), and (23), we have the following equivalent inequalities with the best possible constant factor \(\frac{3}{2}B(\lambda _{1},\lambda _{2})\):

$$\begin{aligned}& \sum_{n = 1}^{\infty } \sum _{m = 1}^{\infty } \frac{a_{m}b_{n}}{(\sqrt[3]{m^{2}} + \sqrt[3]{n^{2}})^{\lambda }} \\& \quad > \frac{3}{2}B(\lambda _{1},\lambda _{2}) \\& \qquad {}\times \Biggl[\sum_{m = 1}^{\infty } \biggl(1 - O\biggl(\frac{1}{m^{2\lambda _{2}/3}}\biggr)\biggr)m^{p(1 - \frac{2\lambda _{1}}{3}) - 1} a_{m}^{p}\Biggr]^{\frac{1}{p}}\Biggl[\sum _{n = 1}^{\infty } n^{q(1 - \frac{2\lambda _{2}}{3}) - 1} b_{n}^{q} \Biggr]^{\frac{1}{q}}, \end{aligned}$$
(30)
$$\begin{aligned}& \Biggl\{ \sum_{n = 1}^{\infty } n^{\frac{2p\lambda _{2}}{3} - 1} \Biggl[\sum_{m = 1}^{\infty } \frac{1}{(\sqrt[3]{m^{2}} + \sqrt[3]{n^{2}})^{\lambda }} a_{m} \Biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\& \quad > \frac{3}{2}B(\lambda _{1},\lambda _{2}) \Biggl[\sum_{m = 1}^{\infty } \biggl(1 - O\biggl( \frac{1}{m^{2\lambda _{2}/3}}\biggr)\biggr)m^{p(1 - \frac{2\lambda _{1}}{3}) - 1} a_{m}^{p} \Biggr]^{\frac{1}{p}}, \end{aligned}$$
(31)
$$\begin{aligned}& \Biggl\{ \sum_{m = 1}^{\infty } \frac{m^{2q\lambda _{1}/3 - 1}}{(1 - O(\frac{1}{m^{2\lambda _{2}/3}}))^{q - 1}}\Biggl[\sum_{n = 1}^{\infty } \frac{b_{n}}{(\sqrt[3]{m^{2}} + \sqrt[3]{n^{2}})^{\lambda }} \Biggr]^{q}\Biggr\} ^{\frac{1}{q}} \\& \quad > \frac{3}{2}B(\lambda _{1},\lambda _{2}) \Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \frac{2\lambda _{2}}{3}) - 1} b_{n}^{q}\Biggr]^{\frac{1}{q}}. \end{aligned}$$
(32)

Conclusions

In this paper, by virtue of the symmetry principle, by means of the techniques of real analysis and Euler–Maclaurin summation formula, we construct proper weight coefficients and use them to establish a reverse Hardy–Hilbert inequality with the power function as intermediate variables and the equivalent forms in Lemma 2 and Theorem 1. Then, we obtain some equivalent statements of the best possible constant factor related to several parameters in Theorem 2. Finally, we illustrate how the obtained results can generate some particular reverse Hardy–Hilbert inequalities in Remark 3. The lemmas and theorems provide an extensive account of this type of inequalities.

Availability of data and materials

The data used to support the findings of this study are included within the article.

References

  1. Hardy, G.H., Littlewood, J.E., Polya, G.: Inequalities. Cambridge University Press, Cambridge (1934)

    MATH  Google Scholar 

  2. Krnić, M., Pečarić, J.: Extension of Hilbert’s inequality. J. Math. Anal. Appl. 324(1), 150–160 (2006)

    MathSciNet  Article  Google Scholar 

  3. Yang, B.: On a generalization of Hilbert double series theorem. J. Nanjing Univ. Math. Biq. 18(1), 145–152 (2001)

    MathSciNet  MATH  Google Scholar 

  4. Adiyasuren, V., Batbold, T., Azar, L.E.: A new discrete Hilbert-type inequality involving partial sums. J. Inequal. Appl. 2019, 127 (2019)

    MathSciNet  Article  Google Scholar 

  5. Yang, B.C.: The Norm of Operator and Hilbert-Type Inequalities. Science Press, Beijing (2009)

    Google Scholar 

  6. Krnić, M., Pečarić, J.: General Hilbert’s and Hardy’s inequalities. Math. Inequal. Appl. 8(1), 29–51 (2005)

    MathSciNet  MATH  Google Scholar 

  7. Perić, I., Vuković, P.: Multiple Hilbert’s type inequalities with a homogeneous kernel. Banach J. Math. Anal. 5(2), 33–43 (2011)

    MathSciNet  Article  Google Scholar 

  8. Huang, Q.L.: A new extension of Hardy–Hilbert-type inequality. J. Inequal. Appl. 2015, 397 (2015)

    MathSciNet  Article  Google Scholar 

  9. He, B.: A multiple Hilbert-type discrete inequality with a new kernel and best possible constant factor. J. Math. Anal. Appl. 431, 889–902 (2015)

    MathSciNet  Article  Google Scholar 

  10. Xu, J.S.: Hardy–Hilbert’s inequalities with two parameters. Adv. Math. 36(2), 63–76 (2007)

    MathSciNet  Google Scholar 

  11. Xie, Z.T., Zeng, Z., Sun, Y.F.: A new Hilbert-type inequality with the homogeneous kernel of degree −2. Adv. Appl. Math. Sci. 12(7), 391–401 (2013)

    MathSciNet  MATH  Google Scholar 

  12. Zhen, Z., Raja Rama Gandhi, K., Xie, Z.T.: A new Hilbert-type inequality with the homogeneous kernel of degree −2 and with the integral. Bull. Math. Sci. Appl. 3(1), 11–20 (2014)

    Google Scholar 

  13. Xin, D.M.: A Hilbert-type integral inequality with the homogeneous kernel of zero degree. Math. Theory Appl. 30(2), 70–74 (2010)

    MathSciNet  Google Scholar 

  14. Azar, L.E.: The connection between Hilbert and Hardy inequalities. J. Inequal. Appl. 2013, 452 (2013)

    MathSciNet  Article  Google Scholar 

  15. Adiyasuren, V., Batbold, T., Krnić, M.: Hilbert-type inequalities involving differential operators, the best constants and applications. Math. Inequal. Appl. 18, 111–124 (2015)

    MathSciNet  MATH  Google Scholar 

  16. Batbold, T., Azar, L.E.: A new form of Hilbert integral inequality. J. Math. Inequal. 12(1), 379–390 (2018)

    MathSciNet  Article  Google Scholar 

  17. Rassias, M.T., Yang, B.C.: On half-discrete Hilbert’s inequality. Appl. Math. Comput. 220, 75–93 (2013)

    MathSciNet  MATH  Google Scholar 

  18. Yang, B.C., Krnić, M.: A half-discrete Hilbert-type inequality with a general homogeneous kernel of degree 0. J. Math. Inequal. 6(3), 401–417 (2012)

    MathSciNet  MATH  Google Scholar 

  19. Rassias, M.T., Yang, B.C.: A multidimensional half-discrete Hilbert-type inequality and the Riemann zeta function. Appl. Math. Comput. 225, 263–277 (2013)

    MathSciNet  MATH  Google Scholar 

  20. Rassias, M.T., Yang, B.C.: On a multidimensional half-discrete Hilbert – type inequality related to the hyperbolic cotangent function. Appl. Math. Comput. 242, 800–813 (2013)

    MathSciNet  MATH  Google Scholar 

  21. Yang, B.C., Debnath, L.: Half-Discrete Hilbert-Type Inequalities. World Scientific, Singapore (2014)

    Book  Google Scholar 

  22. Liao, J.Q., Wu, S.H., Yang, B.C.: On a new half-discrete Hilbert-type inequality involving the variable upper limit integral and the partial sum. Mathematics 8, 229 (2020). https://doi.org/10.3390/math8020229

    Article  Google Scholar 

  23. Hong, Y., Wen, Y.M.: A necessary and sufficient condition of that Hilbert type series inequality with homogeneous kernel has the best constant factor. Ann. Math. 37A(3), 329–336 (2016)

    MATH  Google Scholar 

  24. Hong, Y.: On the structure character of Hilbert’s type integral inequality with homogeneous kernel and application. J. Jilin Univ. Sci. Ed. 55(2), 189–194 (2017)

    Google Scholar 

  25. Hong, Y., Huang, Q.L., Yang, B.C., Liao, J.L.: The necessary and sufficient conditions for the existence of a kind of Hilbert-type multiple integral inequality with the non-homogeneous kernel and its applications. J. Inequal. Appl. 2017, 316 (2017)

    MathSciNet  Article  Google Scholar 

  26. Xin, D.M., Yang, B.C., Wang, A.Z.: Equivalent property of a Hilbert-type integral inequality related to the beta function in the whole plane. J. Funct. Spaces 2018, Article ID 2691816 (2018)

    MathSciNet  MATH  Google Scholar 

  27. Hong, Y., He, B., Yang, B.C.: Necessary and sufficient conditions for the validity of Hilbert type integral inequalities with a class of quasi-homogeneous kernels and its application in operator theory. J. Math. Inequal. 12(3), 777–788 (2018)

    MathSciNet  Article  Google Scholar 

  28. Huang, Z.X., Yang, B.C.: Equivalent property of a half-discrete Hilbert’s inequality with parameters. J. Inequal. Appl. 2018, 333 (2018)

    MathSciNet  Article  Google Scholar 

  29. Yang, B.C., Wu, S.H., Wang, A.Z.: On a reverse half-discrete Hardy–Hilbert’s inequality with parameters. Mathematics 7, 1054 (2019)

    Article  Google Scholar 

  30. Yang, B.C., Wu, S.H., Chen, Q.: On an extended Hardy–Littlewood–Polya’s inequality. AIMS Math. 5(2), 1550–1561 (2020)

    MathSciNet  Article  Google Scholar 

  31. Wang, A.Z., Yang, B.C., Chen, Q.: Equivalent properties of a reverse’s half-discrete Hilbert’s inequality. J. Inequal. Appl. 2019, 279 (2019)

    MathSciNet  Article  Google Scholar 

  32. Luo, R.C., Yang, B.C.: Parameterized discrete Hilbert-type inequalities with intermediate variables. J. Inequal. Appl. 2019, 142 (2019)

    MathSciNet  Article  Google Scholar 

  33. Huang, Z.X., Shi, Y.P., Yang, B.C.: On a reverse extended Hardy–Hilbert’s inequality. J. Inequal. Appl. 2020, 68 (2020)

    MathSciNet  Article  Google Scholar 

  34. Kuang, J.C.: Applied Inequalities. Shangdong Science and Technology Press, Jinan (2004)

    Google Scholar 

Download references

Acknowledgements

The authors thank the referee for their useful proposal to reform the paper.

Funding

This work is supported by the National Natural Science Foundation (Nos. 11961021, 11561019), Hechi University Research Foundation for Advanced Talents under Grant (2021GCC024), and Science and Technology Planning Project Item of Guangzhou City (No. 201707010229). We are grateful for this help.

Author information

Affiliations

Authors

Contributions

BY carried out the mathematical studies, participated in the sequence alignment, and drafted the manuscript. XH and RL participated in the design of the study and performed the numerical analysis. All authors read and approved the final manuscript.

Corresponding author

Correspondence to Xingshou Huang.

Ethics declarations

Competing interests

The authors declare that they have no competing interests.

Rights and permissions

Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/.

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Huang, X., Yang, B. & Luo, R. A new reverse Hardy–Hilbert inequality with the power function as intermediate variables. J Inequal Appl 2022, 49 (2022). https://doi.org/10.1186/s13660-022-02784-2

Download citation

  • Received:

  • Accepted:

  • Published:

  • DOI: https://doi.org/10.1186/s13660-022-02784-2

MSC

  • 26D15
  • 26D10
  • 47A05

Keywords

  • Weight coefficient
  • Hardy–Hilbert inequality
  • Equivalent statement
  • Parameter
  • Power function
  • Reverse